2021
DOI: 10.1007/s11325-021-02476-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obstructive sleep apnea on clinical outcomes in patients hospitalized with COVID-19

Abstract: Purpose Data from large patient registry studies suggested an increased incidence and increased mortality in coronavirus disease-2019 (COVID-19) in patients with a history of obstructive sleep apnea (OSA). This study aimed to compare the prevalence of OSA in patients with and without COVID-19 among patients admitted to the same hospital in the same time period. In addition, the impact of OSA on clinical outcomes of COVID-19 infection was investigated. Methods Observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Moreover, we believe that neck circumference could outperform the prognostic predictive value of BMI among COVID-19 patients, being more associated with a specific fat distribution pattern, thus reflecting a “bad” obesity distribution pattern. Interestingly, a large neck circumference has been significantly associated with the prevalence of obstructive sleep apnea syndrome [ 17 ]. According to the literature data, obstructive sleep apnea syndrome occurs in 2–4% of adults, increasing by 2.5 times the risk of sudden death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we believe that neck circumference could outperform the prognostic predictive value of BMI among COVID-19 patients, being more associated with a specific fat distribution pattern, thus reflecting a “bad” obesity distribution pattern. Interestingly, a large neck circumference has been significantly associated with the prevalence of obstructive sleep apnea syndrome [ 17 ]. According to the literature data, obstructive sleep apnea syndrome occurs in 2–4% of adults, increasing by 2.5 times the risk of sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature data, obstructive sleep apnea syndrome occurs in 2–4% of adults, increasing by 2.5 times the risk of sudden death. When looking at SARS-CoV-2-infected patients, a recent study showed that there was an increased risk of mortality in COVID-19 patients with obstructive sleep apnea syndrome (OR = 2.59; 95% CI 1.218–5.507) independently from BMI, male gender, age, diabetes, cardiovascular diseases, and obstructive lung disease [ 17 ]. It is possible that part of the risk is attributable to the fact that, since gasping is a common phenomenon in patients with obstructive sleep apnea syndrome, this can predispose to aspiration of viral particles [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the authors descriptively reviewed the potential relationship between obstructive sleep apnoea (OSA) and the risk for mortality among patients with coronavirus disease 2019 (COVID-19), but failed to quantitatively address this association. To our knowledge, some original studies reported that OSA was significantly linked to an elevated risk for fatal COVID-19 ( 2 , 3 , 4 ), while some others observed non-significant relationship between OSA and fatal COVID-19 ( 5 , 6 , 7 ). Therefore, there is an urgent need to evaluate the association of OSA with fatal COVID-19 by performing a quantitative meta-analysis.…”
mentioning
confidence: 87%
“…383 articles were identified through a preliminary literature search, 152 articles remained after eliminating duplicates, 107 articles were excluded after reading the title and abstract, 45 full-text articles were assessed for eligibility, in the end, 13 articles ( 2 , 3 , 4 , 5 , 6 , 7 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ) with 31,933 COVID-19 patients were included in this study. Of these thirteen studies, four studies were prospective and nine studies were retrospective.…”
mentioning
confidence: 99%
“…To date, most of the data published on the risk factors for the pneumonia in COVID-19 and long-term sequelae (as example: male gender, age, obesity, hypertension, diabetes) are also recognized as clinical risk factor for increased risk of obstructive sleep apnea (OSA) ( 8 11 ). However, data about the association between OSA and COVID-19 is limited to few studies, including indirect measures such as questionnaires, or secondary analysis of databases ( 1 , 8 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%